Synthesis and Characterization of Bioplastic from Chitosan-Ganyong Starch (Canna edulis) - Agung Nugroho Catur Saputro; Arruum Linggar Ovita (Program Studi Pendidikan Kimia FKIP Universitas Sebelas Maret, 2017)
The purpose of this study was to produced bioplastic from chitosan-ganyong starch and compare its quality to commercial biodegradable plastic. This research was carried out by experimental method in laboratory. Making bioplastic film was done by dissolving, blending, printing, drying, and neutralizing process. Characterization of bioplastic film was performed by tensile strength test,% elongation, thickness, swelling, solubility, biodegradability and functional group analysis with FTIR. The produced bioplastic characterizations were compared to commercial biodegradable plastics. The results concluded that the qualities of bioplastic chitosan-ganyong starch are higher than commercial biodegradable plastics on tensile strength parameter (53,9644 Mpa : 18,4109 MPa),% elongation (1,8066 % : 3,7025%), and degradation ability (5 days : 30 days); but lower in thickness parameters (0.0350 mm: 0.0140 mm), % swelling (0.275%: 0.010%), and solubility (0.10%: 0.05%).